Readiness and Service Model Exploration for Chronic Kidney Disease Telemonitoring at Public Hospital in Bengkulu, Indonesia - Nurhidayati, Nurhidayati; Arini, Merita; Wan Mamat, Wan Hasliza (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Public hospitals in Bengkulu lack health workers in hemodialysis units, making services not optimal, and the quality of life of chronic kidney disease patients is not controlled. Thus, telemonitoring should be an alternative to a remote health service. This study aimed to determine readiness and explore the telemonitoring service model needed in public hospitals in Bengkulu. This qualitative research used group discussion forums and in-depth interviews with 24 informants, consisting of management and health workers in the hemodialysis unit, recruited by purposive sampling. Audio recordings, verbatim transcripts, and thematic analyses were carried out. Public hospitals in Bengkulu are ready to carry out telemonitoring services regarding potential reasons, expectations from health workers, and benefits to implement as alternative solutions to improve service quality—inhibiting factors such as support tools, patients, health workers, organization, and low understanding of telemonitoring. Supporting factors are the adequacy of basic infrastructure facilities, the allocation of funds, and the required service models such as materials, supporting devices, and service settings. In conclusion, a public hospital in Bengkulu meets the readiness indicators of telemonitoring services for chronic kidney disease patients from a health worker’s perspective. Potential supporting factors need to be improved, inhibiting factors need to be anticipated, and the required service model needs to be described.